FEATURES OF THE RELATIONSHIP OF JUDGES AND CHAIRMAN OF COURTS IN THE RUSSIAN FEDERATION - M. Gubaidullina, Elvira; A. Gubaidullin, Artur (Gênero & Direito, 2019)
The issue of ensuring the real independence of the court is a multidimensional one, and perhaps this is really an area, in which it is impossible to solve all problems at once, by adopting one single (albeit very thoughtful) law. This is an area in which translational movement is a necessary component of success. In any case, it is difficult to argue with the fact that the quality of the judicial system at the moment and its gradual development in the future is an important milestone in the development of the state and society [1].The purpose of this work is as follows: consideration of the current legislative provisions governing the legal status of the presiding judge, identification of interaction areas between ordinary judges and presiding judges, analysis of proposed changes to the legislation governing the activities of court leaders and assessment of the possible consequences of the adoption of these provisions of the law. Based on the review results, it is concluded that the most optimal way to ensure the independence of the judiciary in the Russian Federation is the real irremovability of judges when they are appointed without limiting the term of office, provided that a high-quality, effective and transparent system for evaluating their work is developed, with a clear establishment of the level and procedure for bringing to justice, up to the possibility of deprivation of the corresponding position or status.